The Effect of Socio-Economic Factors on Property Crimes in the Gerbangkerto- susila Area - Raviadi, Krista Amanda; Huda, Syamsul; Perdana, Putra (MediaTrend, 2024)
Crime is a severe problem for every region because it harms many people, especially property crimes. Factors such as poverty, unemployment, and education are some of the factors that are assumed to influence crime in a country or region. This research aims to determine the influence of poverty levels on property crimes, the impact of unemployment levels on property crimes, the influence of average years of schooling on property crimes, and the influence of poverty levels, unemployment rates, and average years of education together against property crimes. The research method uses panel data regression with the Fixed Effect Model (FEM). The data from the East Java Central Statistics Agency, namely data from the Gerbangkertosusila Region (Gresik, Bangkalan, Mojokerto, Surabaya, Sidoarjo, Lamongan) for 2018 - 2022. The research results show that the poverty level significantly affects property crime, and the unemployment rate has a negative impact. Not significantly on property crimes, and average years of schooling significantly negatively affect property crimes.